The use of Google meet in learning Arabic language during COVID-19 Pandemic / Nur Shuhadak Ismail ...[et al.] - Ismail, Nur Shuhadak; Ahmad, Nor Zahidah; Fauzi, Asma'; Mohd, Khairun Nisaa (UiTM Press, 2021)
The Covid-19 pandemic has shifted the education landscape from conventional learning to online learning. As reported by the United Nations, Covid-19 has affected roughly 1.6 billion learners. Most instructors need to deliver their teaching activities online including instructors in higher education institutions as all higher education institutions in Malaysia are also closed due to this pandemic. Hence, the academicians need to prepare themselves with the technological knowledge and skills in providing an effective learning environment for students while students need to adapt to this new educational process. There are various online platforms that have been implemented to engage the students in language online learning and one of them is Google Meet. Google Meet is widely used in many higher education institutions to disseminate knowledge. The two theories used in this study are TAM (Technology Acceptance Model) and CoI (Community of Inquiry) to guide the implementation of the use of Google Meet in Arabic language learning. This paper analyses the advantages and disadvantages of using Google Meet in language learning and the implementation of Arabic language learning by employing it.